Peppers: Vegetable and Spice Capsicums (2nd Edition) - Bosland, Paul W (CABI, 2014)
A vast amount of research on peppers has been conducted since the original edition of Peppers: Vegetable and Spice Capsicums was first set to print and, as a result, our understanding of this fascinating crop has grown. Worldwide production has also grown. Peppers are multifaceted and iconic. Their story is intriguing, and their shapes, sizes, colors, flavors, heat levels, nutritional properties and uses are as diverse as the places where they are grown and the people who grow them. The genus Capsicum is a source of products, both hot and not, that are utilized around the globe. The capsicums are unique in being used as both a vegetable (or, strictly, a fruit) and a spice. They provide spicy heat, flavoring and color to foods. They also provide essential vitamins, minerals and nutrients. Pepper extracts are used in pharmaceuticals, cosmetic products, paints and pepper sprays. In addition to their use as food, condiment and medicine, peppers are used for their ornamental beauty. In order to understand how this crop has come to be used so widely and in so many ways, we must begin with an understanding of its origins.